2018
DOI: 10.1002/jcla.22643
|View full text |Cite
|
Sign up to set email alerts
|

Internal quality control status for BNP and NT‐proBNP in China from 2014 to 2017

Abstract: The imprecision performance of measurement of BNP and NT-proBNP has improved with decreasing of current CVs and increasing of pass rates in 4 years. However, it still needs continual improvement. Clinical laboratories in China should take active actions to promote performance of BNP and NT-proBNP measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the multicenter cohort study, the NT-proBNP measurement was based on four assays, and the variation among laboratories was not evaluated. However, the four assays used same antibodies and calibrator from the same vendor, and previous data showed that the between-method variability of NT-proBNP was not the predominant component of total variability [ 43 ], and the imprecision performance of measurement of NT-proBNP in China had improved with the significant decrease of current coefficient of variations [ 44 ]. Finally, although the validation cohort of the present study allowed the CRH score to be externally tested in a population with a distinct age distribution, it had relatively shorter duration of follow up compared with the derivation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In the multicenter cohort study, the NT-proBNP measurement was based on four assays, and the variation among laboratories was not evaluated. However, the four assays used same antibodies and calibrator from the same vendor, and previous data showed that the between-method variability of NT-proBNP was not the predominant component of total variability [ 43 ], and the imprecision performance of measurement of NT-proBNP in China had improved with the significant decrease of current coefficient of variations [ 44 ]. Finally, although the validation cohort of the present study allowed the CRH score to be externally tested in a population with a distinct age distribution, it had relatively shorter duration of follow up compared with the derivation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…13 As per ISO15139, quality indicators are defined as a "measure of the degree to which a set of inherent characteristics fulfil requirements". 15 As one of the quality indicators in the analysis phase, CV was used as an indicator of quality requirement/performance.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage CV for monitoring the imprecision of measurements reflects the quality of the laboratory analysis phase [22]. In a study of 72 laboratories in China, the findings showed that using the Siemens BNP kits, the median CV ranged from 4.87% (interquartile range [IQR] 2.38) to 5.17% (IQR 3.33) [23].…”
Section: Discussionmentioning
confidence: 99%